Electrochemical Properties of Ru Polypyridyl Phosphonates. Issue 11 (22nd February 2023) - Herath, Hashini N. K.; MacRae, Austin L.; Ugrinov, Angel; Morello, Glenn R.; Parent, Alexander R.
Abstract: [Ru(bpyPO3 H2 )(bpy)Cl]Cl (bpyPO3 H2 =6, 6'‐bipyridin‐2‐yl)phosphonic acid) and [Ru(tpy)(MepyPO3 H2 )Cl]Cl (MepyPO3 H2 =(pyridin‐2‐ylmethyl)phosphonic acid) were synthesized and characterized spectroscopically and electrochemically. Each compound was found to exhibit proton‐coupled electron transfer (PCET). In the case of [Ru(bpyPO3 H2 )(bpy)Cl]Cl, a Ru(V/IV) couple was detected at 1.4 V vs . NHE. Each complex was tested for its ability to catalyze C−H bond oxidation using a variety of sacrificial oxidants, and it was found that under aqueous conditions [Ru(bpyPO3 H2 )(bpy)Cl]Cl oxidizes secondary C−H bonds using sodium periodate (NaIO4 ) as the primary oxidant. Abstract : Ru complexes containing polypyridyl phosphonate ligands were synthesized and characterized spectroscopically and electrochemically. Each compound was found to exhibit proton‐coupled electron transfer (PCET).